As sagradas de Asherah e YHWH: narrativa e memória do sacerdócio feminino no templo de Jerusalém - Matos, Sue’Hellen Monteiro de (2022)
This research analyzes the female priesthood in the temple of Jerusalem at the service of the divine couple, Asherah and YHWH. This service has as its main object the narrative of 2 Kings 23:4-14. To this object were added analyses of the archaeological evidence about the cult of Asherah and the divine couple, as well as the examination of textual and iconographic sources that ascertain the various priestly categories of women in the Ancient Near East. Considering the results of these analyses it is concluded that "the women who wove garments to Asherah" mentioned in the biblical text (v.7) would be, not only priestesses of Asherah, but also of YHWH. With this, the thesis argues for the legitimacy of the cultic space of women in the main temple of Judah, Jerusalem. They took part not only in the domestic setting of private religion, but also in the worship space of public religion, also acting in spaces of power. However, although the "women who wove robes to Asherah" are priestesses, they are not named as such. This is because there is a gendered memory politics carried out by the biblical writers who selected what to describe, how to describe them, and what has to be forgotten. Therefore, we have analyzed the narrative construction and gendered memory politics of Josiah's 'victorious' discourse that constructs a repudiation of women, the Goddess, other Gods, and their priests, all expelled in his exclusively Javish religious restructuring. This research was based on a bibliographical survey of works published in Brazil and abroad, which inform about the current stage of research on Asherah and her priestesses, both from the point of view of biblical literature and archaeological evidence. The text of 2 Kings 23:4-14 was analyzed through exegesis from a feminist perspective. This methodology includes the steps of the historical-critical method and form criticism, with a discussion of power relations between the sexes within a kyriarchal culture. Finally, the process of silencing, concealing, and disqualifying the women who served the Goddess Asherah, and also YHWH, was discussed, as well as the violent language against the Goddess itself. This discussion was based on the theoretical assumptions of Paul Ricoeur about the politics of memory and of Elisabeth Schüssler Fiorenza about the hermeneutics of suspicion and remembrance. It is concluded that there is a gender politics of memory used by the biblical redactors, which erases the memory of the Goddess Asherah and disassociates her from YHWH, as well as invisibilizes female priesthood in the Jerusalem temple, denying women the sacred space and power that had once been occupied by them. Consequently, a new politics of memory was elaborated: there was an official worship of the divine couple in Jerusalem, in which women and men were part of the priesthood. (AU)